A retrospective analysis of trends of HIV and syphilis among blood donors in north India - Sehgal, P. K.; Garg, Dinesh (International Journal of Research in Medical Sciences, 2017)
Background: In India, it is mandatory to screen blood donors for HIV, hepatitis B, hepatitis C, syphilis and malaria. The donor screening strategies include taking the elaborate medical history, performing preliminary clinical examination and screening for infectious markers. The infectious markers include anti-HIV (1 and 2) antibodies, hepatitis B surface antigen (HBsAg), anti-hepatitis C virus antibodies, and malaria antigens, such as histidine rich protein (HRP) and pan-aldolase. National adult (15-49 years) HIV prevalence is estimated at 0.26% (0.22%-0.32%) in 20155 (0.30% among males and 0.22% among females). The objective of this study was to be carried out with the aim to find out the seroprevalence of HIV infection and its trend among the blood donors a hospital based blood transfusion service set up in north India over a period of six years. Methods: It was record based retrospective study from 2010 to 2015. Before donation "blood donation form" had been filled by every donor and this form had particulars about age, gender, address, and occupation, date of previous donation, any illness and medical treatment taken. The donor blood samples were collected at the time of blood donation from the primary bag and tested for the presence of HIV using enzyme linked immunosorbent assay (ELISA). All donors were subjected to a pre-test counselling which was done by qualified staff trained to screen donors for blood donation. Results: A prevalence of 0.21% of HIV was seen among the donors from the period 2010-2015. The trend of HIV prevalence among donors has been fluctuating while ranging from 0.13% to 0.34%. Conclusions: HIV remains the major threat for transfusion transmitted infections in India. For a safe blood service in our country, where comprehensive laboratory tests are neither possible nor pragmatic, it is best to switch over to 100% voluntary donations, as it is now established that only voluntary non-remunerated regular donation is the safest. Thus, one of our key strategies to enhance blood safety is to focus on motivating non-remunerated blood donors and phasing out even replacement donors.